Targetoid hepatic observations on gadoxetic acid-enhanced MRI using LI-RADS version 2018: emphasis on hepatocellular carcinomas assigned to the LR-M category - Park, H. J.; Kim, Y. K.; Cha, D. I.; Ko, S. E.; Kim, S.; Lee, E. S.; Ahn, S. (Clinical Radiology, 2020)
AIM: To determine useful imaging features for differentiating hepatocellular carcinoma (HCC) categorised as LR-M from non-HCC malignancies in using the Liver Imaging-Reporting and Data System (LI-RADS) version 2018 on gadoxetic acid-enhanced magnetic resonance imaging (MRI). MATERIALS AND METHODS: Patients at high-risk for HCC with surgically confirmed HCCs (n=131) and non-HCC malignancies (n=90) and who had undergone gadoxetic acid-enhanced MRI were included. LI-RADS categories were assigned to identify hepatic observations defined as LR-M by two radiologists. Major and ancillary imaging features of hepatic observation with targetoid appearance including intratumoural septa were compared between HCCs and non-HCC malignancies. A classification tree analysis (CTA) was applied to differentiate high-risk HCCs from non-HCC malignancies in the LR-M category. RESULTS: A total of 36 HCCs (27.5%) and 70 non-HCC malignancies (77.8%) were assigned as LR-M. An enhancing capsule (p=0.0293), blood products in the mass (p=0.0393), non-targetoid restriction (p=0.018), and a septum (p=0.0053) were significantly predictive of HCC. On CTA, the presence of a septum was an initial predictor for a high probability of HCC followed by non-targetoid restriction. The CTA model has a sensitivity of 63.9%, specificity of 90%, and accuracy of 81.1% for differentiating HCC assigned LR-M from non-HCC malignancy. CONCLUSION: A considerable proportion of HCCs could have been categorised as LR-M as they had a targetoid appearance on gadoxetic acid-enhanced MRI. An intratumoural septum and non-targetoid restriction as well as enhancing capsule and blood products in the mass may be useful for differentiating HCC assigned to LR-M from non-HCC malignancy on gadoxetic acid-enhanced MRI.
Keywords: Carcinoma, Hepatocellular; Contrast Media; Diagnosis, Differential; Female; Gadolinium DTPA; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Retrospective Studies; Sensitivity and Specificity